2008
DOI: 10.1007/s11060-008-9593-6
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity from chemoradiotherapy in older patients with glioblastoma multiforme

Abstract: Elderly patients with GBM treated with chemoradiotherapy can be expected to experience significant toxicity. Large randomized trials will be necessary to determine whether chemoradiotherapy prolongs the survival of elderly patients and whether MGMT promoter status predicts benefit from temozolomide in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 33 publications
1
90
0
Order By: Relevance
“…31 Sijben et al reported that the MGMT gene promoter was hypermethylated in 13/29 (45%) cases in their series of 39 patients aged 65 or older. 21 Median OS and median progression-free survival (PFS) times were not statistically different for methylated (7.4 and 4.5 months, respectively) and unmethylated (7.3 and 5.5 months, respectively) cases. 21 Gerstner et al found that 37/64 (57.8%) patients aged 70 or older with GB had methylation of the MGMT promoter, similar to the rate of 44.7% seen in the EORTC-NCIC trial.…”
Section: Prognostic Factorsmentioning
confidence: 94%
See 3 more Smart Citations
“…31 Sijben et al reported that the MGMT gene promoter was hypermethylated in 13/29 (45%) cases in their series of 39 patients aged 65 or older. 21 Median OS and median progression-free survival (PFS) times were not statistically different for methylated (7.4 and 4.5 months, respectively) and unmethylated (7.3 and 5.5 months, respectively) cases. 21 Gerstner et al found that 37/64 (57.8%) patients aged 70 or older with GB had methylation of the MGMT promoter, similar to the rate of 44.7% seen in the EORTC-NCIC trial.…”
Section: Prognostic Factorsmentioning
confidence: 94%
“…21 Median OS and median progression-free survival (PFS) times were not statistically different for methylated (7.4 and 4.5 months, respectively) and unmethylated (7.3 and 5.5 months, respectively) cases. 21 Gerstner et al found that 37/64 (57.8%) patients aged 70 or older with GB had methylation of the MGMT promoter, similar to the rate of 44.7% seen in the EORTC-NCIC trial. 24,30 Age, extent of resection, KPS, and MGMT promoter methylation were associated with a reduced hazard for progression and death in a multivariate Cox model in this cohort of 64 elderly patients.…”
Section: Prognostic Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…That shorter os is likely multifactorial and reflects differing tumour biology in elderly patients, as well as differences in treatment patterns and tolerance of therapy [6][7][8] . Many elderly or frail patients are unable to tolerate combined chemoradiotherapy, and toxicities-including severe fatigue, myelosuppression, and infections-are common 9 . As a result, investigators have been led to explore alternative treatment strategies in older gbm patients, including hypofractionated radiotherapy 10,11 and temozolomide monotherapy 12 .…”
Section: Introductionmentioning
confidence: 99%